The impact of information technology and knowledge-oriented management on the operational effectiveness in Polish hospitals - Chluski, Andrzej (Business Informatics, 2016)
The aim of this paper was to present the results of an evaluation of the effect of knowledge-oriented management and level of information technology on the operational effectiveness in Polish hospitals. The data were collected using a questionnaire survey carried out among managers in Polish hospitals. Structural modelling was employed to analyse the data collected. The structural model proposed in the study turned out to fit the data very well, thus demonstrating the positive and cause-and-effect correlations between the level of IT, knowledge-oriented management and operational effectiveness in Polish hospitals
Informatyka Ekonomiczna = Business Informatics, 2016, Nr 1 (39), s. 23-32
Keywords: information technology; knowledge-oriented management; operational efficiency of hospitals; healthcare management; technologie informacyjne; zarządzanie zorientowane na wiedzę; efektywność działalności szpitala; zarządzanie opieką zdrowotną